Determination of Stature by Palm Length in Central India - Keche, Atul S; Mohite, Prakash M; Keche , Harsha A (Journal of Indian Academy of Forensic Medicine, 2016)
Different parameters like Age, Sex, Race, Stature etc are used for identification from fragmented  remains. Identification of an individual from mutilated or distorted or fragmented remains is a difficult task.  Almost every body part bears more or less constant relationship with stature. Similarly palm length also  has a definite correlation with stature of an individual. Considering this fact the present study is based on  measurement of palm length of boys and girls in the age group of 19-25 years belonging to the same  geographical area. Measurements were analyzed statistically. Linear regression equations were derived  and multiplication factors (16.94 for males & 17.51 for females) were calculated. The study shows that  palm length bears a significant relation to stature and can be an important tool for stature estimation in  medico-legal cases & anthropology. Also it can be shown that the measurement and formulae for males  and females are different. That is formula which is obtained for one sex cannot be applied to the other sex  for getting the desired results.
Keywords: Identification; Palm length; Stature; Multiplication factor; Linear regression